The Correlation Between Students’ Self-Esteem And Students’ Speaking Skill - Sholah, Hanif Maulaniam; Ilmi, Izzatul (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
One among many indicators of successful second language acquisition (SLA) is the ability to speak in the target language since learner’s ability in producing a speech implies that they have a good communicative competence. This study was a kind of correlational research designed which focused on knowing the correlation between students’ self-esteem as independent variable and speaking ability as dependent variable which used quantitative method. Based on the degree of correlation coefficient, value 0,763 of the correlation coefficient showed that there was a strong or highly significant positive correlation between students’ self-esteem and students’ speaking skill. From the result, it can be said that self-esteem influenced or related with speaking skill. Theoretically, self-esteem take a role to manage, maintain, and develop students by the challenges of learning goals. Besides, this proof also expects special attention to aspects of psychology that can be started by the teacher itself. So, the results of learning will also be more maximal and can be designed the right learning method.